2017
DOI: 10.1021/acs.biochem.7b00850
|View full text |Cite
|
Sign up to set email alerts
|

A Cooperative Folding Unit as the Structural Link for Energetic Coupling within a Protein

Abstract: Previously, we demonstrated that binding of a ligand to Escherichia coli cofactor-dependent phosphoglycerate mutase (dPGM), a homodimeric protein, is energetically coupled with dimerization. The equilibrium unfolding of dPGM occurs with a stable, monomeric intermediate. Binding of several nonsubstrate metabolites stabilizes the dimeric native form over the monomeric intermediate, reducing the population of the intermediate. Both the active site and the dimer interface appear to be unfolded in the intermediate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…While this enzyme was not previously considered to be allosteric, it was recently proposed to function as an allosteric enzyme, whereby dimer stabilization acts as the allosteric signal that is transmitted rather than the more typical binding of a specific effector to an allosteric site. In this case, the ordering and stabilization of the region that contains the lysines acetylated by AcP act as the transmission signal ( 34 , 35 ). While all AcP acetylations occurred on this highly flexible domain of the protein, the KAT acetylation site (K86) was found outside the active site on a small 3 10 -helix near but not directly interacting with the opposite monomer at the dimer interface.…”
Section: Resultsmentioning
confidence: 99%
“…While this enzyme was not previously considered to be allosteric, it was recently proposed to function as an allosteric enzyme, whereby dimer stabilization acts as the allosteric signal that is transmitted rather than the more typical binding of a specific effector to an allosteric site. In this case, the ordering and stabilization of the region that contains the lysines acetylated by AcP act as the transmission signal ( 34 , 35 ). While all AcP acetylations occurred on this highly flexible domain of the protein, the KAT acetylation site (K86) was found outside the active site on a small 3 10 -helix near but not directly interacting with the opposite monomer at the dimer interface.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of Gpm1 is well known, but molecular analyses, aimed at locating binding sites for various ligands have not been performed so far. One study showed a possible important function of ATP in stabilizing the structure and dimerization of the Gpm1 molecule (Chang et al, 2012;Gardner et al, 2017). Our study on the interactions between Gpm1 and ECM proteins revealed possible interaction sites at motifs aa 116-158 for VTR and aa 138-175 for FN, with aa 138-158 sequence binding to both host proteins.…”
Section: Discussionmentioning
confidence: 66%
“…While this enzyme was not previously considered to be allosteric, it was recently proposed to function as an allosteric enzyme, whereby dimer stabilization acts as the allosteric signal that is transmitted rather than the more typical binding of a specific effector to an allosteric site. In this case, the ordering and stabilization of the region that contains the lysines acetylated by AcP acts as the transmission signal (34, 35). While all AcP acetylations occurred on this highly flexible domain of the protein, the KAT acetylation site (K86) was found outside the active site on a small 3 10 -helix near but not directly interacting with the opposite monomer at the dimer interface.…”
Section: Resultsmentioning
confidence: 99%